Eimeria stiedai: Metabolism of lipids, proteins and glucose in experimentally infected rabbits, Oryctolagus cuniculus - Freitas, Fagner L. C.; Yamamoto, Beatriz L.; Freitas, Wagner L. C; Almeida, Katyane S; Machado, Rosangela Z. [UNESP]; Machado, Célio R. [UNESP] (My University, 2010)
Rabbits were experimentally infected with sporulated Eimeria stiedai oocysts. A total of 50 white adult rabbits, New Zealand race, were distributed into two groups: Group A was infected with 1x10 4 sporulated Eimeria stiedai oocysts, while group B was inoculated with distilled water as a control. The animals generally displayed increased levels of total protein, globulin, total cholesterol, LDL-c and triacylglycerols; however, total levels of liver lipids and HDL-c decreased, and plasma glucose levels varied during the experimental period. In sum, Eimeria stiedai infection of rabbits caused a considerable number of changes in the metabolism of lipids, proteins and glucose, which is likely due to direct effects of liver cirrhosis on normal body function.
Keywords: Apicomplexa; Eimeria stiedai; Metabolism; Rabbits.; Animalia; Eimeria; Oryctolagus cuniculus